2021
DOI: 10.1192/j.eurpsy.2021.2251
|View full text |Cite
|
Sign up to set email alerts
|

Capturing adolescents in need of psychiatric care with psychopathological symptoms: A population-based cohort study

Abstract: This peer-reviewed article has been accepted for publication but not yet copyedited or typeset, and so may be subject to change during the production process. The article is considered published and may be cited using its DOI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…In fact, it has been repeatedly confirmed that the long-term trajectory of any mental disorder is highly influenced by treatments provided to patients in the first years of the disease [54][55][56]. Therefore, the early detection and appropriate treatment of any mental disorder is essential to improve the long-term prognosis of patients [57][58][59][60][61][62]. This model must also be applied to other severe mental disorders, including obsessive-compulsive disorder, which has been overlooked and wrongly considered "less" severe compared to psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been repeatedly confirmed that the long-term trajectory of any mental disorder is highly influenced by treatments provided to patients in the first years of the disease [54][55][56]. Therefore, the early detection and appropriate treatment of any mental disorder is essential to improve the long-term prognosis of patients [57][58][59][60][61][62]. This model must also be applied to other severe mental disorders, including obsessive-compulsive disorder, which has been overlooked and wrongly considered "less" severe compared to psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…Psychopathological symptoms were assessed using a modified version of the Brief Symptom Inventory (Derogatis & Melisaratos, 1983 ; Rotstein, Goldenberg, Fund, Levine, & Reichenberg, 2021 ). The inventory covers nine dimensions of psychopathology: psychoticism, paranoid ideation, depression, anxiety, phobic anxiety, somatization, obsession-compulsion, interpersonal sensitivity, hostility (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Our cross-sectional and observational study design cannot discern the causal basis for these findings but helps to refine several testable hypotheses. For example: greater cognitive impairments may partly drive greater psychopathology [63,64] and this effect may be more pronounced in XYY than XXY/KS; greater psychopathology may drive lower performance in IQ tests and this effect may be stronger in XYY than XXY/KS; there may be nonlinear associations between psychopathology and cognitive impairment so that correlations are stronger at the higher levels of psychopathology observed in XYY as compared to XXY/KS (however, see…”
Section: X-and Y-dosage Effects On the Coupling Of Psychopathology An...mentioning
confidence: 99%